Generative AI integration in ELT take-home tasks: Challenges, relevance, and cognitive development at high schools - Sarfita Br Sitepu; Ashadi Ashadi (Universitas Syiah Kuala, 2026)
Generative Artificial Intelligence (GAI) tools, such as ChatGPT, have gained popularity among high school (HS) English language learners (ELLs) in Indonesia. However, the use of ChatGPT in ELT take-home tasks remains underexplored. This study examined its ability to handle different cognitive-level ELT take-home tasks, explored how ChatGPT influences HS ELLs’ cognitive development during task completion, and identified teachers’ perspectives on its influence on these tasks. A descriptive qualitative design was employed, involving twelve HS ELLs and four English teachers. Data were collected through task simulations and semi-structured interviews and were then analyzed thematically to identify patterns in GAI’s impact on ELT. The findings indicate that ChatGPT supports Lower Order Thinking Skills (LOTS) and Middle Order Thinking Skills (MOTS) tasks, which allow ELLs to copy AI-generated responses easily. This suggests that LOTS and MOTS tasks lose their role as take-home tasks, raising concerns about academic integrity. Moreover, teachers agreed that ChatGPT can serve as a constructivist tool to foster deeper engagement. With proper guidance, ELLs can develop strong navigation skills to ensure that AI use enhances their cognitive development. To maintain educational rigor, the study recommends using HOTS tasks with more intricate prompts that foster deeper cognitive engagement and metacognitive skills. This study contributes to maximizing ChatGPT’s potential for meaningful learning experiences for HS ELLs while preserving cognitive development.